Empowering Teachers Through AI-Integrated Pronunciation Training with Google AI Studio: A Community Service Program at SMPN 1 Jongkat, Mempawah Regency - Venny Karolina; Warneri; Aunurrahman; Urai Salam; Haratua Tiur Maria; Eka Ariyati; Muhammad Basri; Farina Nozakiah Tazijan; Siti Fauziana Zakaria; Abdul Azim Mahda; Aiman Zulaikha Mohd Fadzli (Unram Journal of Community Service, 2026)
The integration of artificial intelligence in English language teaching faces implementation challenges despite documented benefits, particularly in resource-limited Indonesian contexts where teachers' digital competence significantly influences adoption. This community service program addressed these gaps through comprehensive technology integration training focused on Google AI Studio for pronunciation instruction at SMPN 1 Jongkat, Mempawah Regency. The program employed a participatory approach combining needs analysis, hands-on training, collaborative workshops, and systematic evaluation involving 19 teachers. Post-training surveys using 5-point Likert scales assessed confidence levels across multiple dimensions of AI-assisted pronunciation instruction. Results demonstrated consistently high confidence levels across most dimensions, with means ranging from 4.26 to 4.74, particularly in using AI-generated speech for listening input and designing speaking activities. However, teachers showed notably lower confidence in self-assessment applications, revealing hesitation in comparing their own pronunciation with AI-generated models. The majority of participants prioritized ease of material development as the primary advantage. Analysis through the Technological Pedagogical Content Knowledge framework indicated successful development of integrated technical and pedagogical competence, though limited articulation of specific implementation strategies suggests need for ongoing professional support. The training successfully established foundational confidence for AI integration while identifying areas requiring continued development to ensure sustainable implementation.